Analysis of the relationship between government’s anti-corruption programs and bribe-giving behavior at the individual level in Indonesia - Agustinus Cahyo Wibowo; Khoirunurrofik Khoirunurrofik (Komisi Pemberantasan Korupsi, 2024)
Research on corruption in Indonesia has primarily focused on institutional corruption, while individual-level bribery remains underexplored. This study analyzes data from the 2020–2021 Anti-Corruption Behavior Survey (SPAK) and other surveys by Statistics Indonesia (BPS) to examine the relationship between the government’s anti-corruption programs and the possibility of individuals in Indonesia engaging in bribery to access public services. The study explores how the programs interact with community perceptions and individual characteristics such as education, gender, marital status, and living area characteristics like Information and Communication Technology (ICT) development and Gross Regional Domestic Product (GRDP). Findings indicate that the anti-corruption program implemented by the government is still limited to community groups with a high chance of committing bribery. Negative interactions are observed between government’s programs and perceptions of anti-corruption in family and public spheres, suggesting that incorporating community perceptions into anti-corruption programs can reduce bribery through rational choice and social norms. It was also found that people with lower education levels, male gender, married status, and living in areas with high ICT development and areas with high GRDP tend to bribe more. At a certain point, increasing age will reduce the chances of bribery. The government should design and implement anti-corruption programs that account for individual and regional characteristics, utilizing both direct and indirect media channels to enhance public perception of anti-corruption and reduce bribe-giving behavior.